2018
DOI: 10.1186/s12955-018-0948-1
|View full text |Cite
|
Sign up to set email alerts
|

Dutch norms for the Strengths and Difficulties Questionnaire (SDQ) – parent form for children aged 2–18 years

Abstract: BackgroundIdentification of children at risk for psychosocial problems is important to be able to provide supportive and tailored care at an early stage. Due to its brevity and wide age range, the Strengths and Difficulties Questionnaire (SDQ) Parent Form is an appropriate instrument for use in paediatric clinical practice as it facilitates assessment of psychosocial functioning from young childhood into adulthood. The aim of the present study was to provide Dutch normative data for the SDQ Parent Form.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
54
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 26 publications
9
54
2
Order By: Relevance
“…The total difficulties score can be dichotomized as being at risk of clinical problems (TDS > 12) or not at risk (< 12). Cutoff was determined based on published norms and measures for borderline and definite clinical risk, as well as identifying scores for the top 20% (characterized as being at risk of clinical problems) in our total sample of 3-year-old children (23,24).…”
Section: Outcome Variables: Mental Health Problemsmentioning
confidence: 99%
“…The total difficulties score can be dichotomized as being at risk of clinical problems (TDS > 12) or not at risk (< 12). Cutoff was determined based on published norms and measures for borderline and definite clinical risk, as well as identifying scores for the top 20% (characterized as being at risk of clinical problems) in our total sample of 3-year-old children (23,24).…”
Section: Outcome Variables: Mental Health Problemsmentioning
confidence: 99%
“…Although the SDQ is commonly used as a screening and research tool in different countries and exists in numerous language versions, normative data are only available from a limited number of countries, ages and informants (see http://www.sdqinfo.org). Previous studies on the psychometric properties of the SDQ have shown that norms vary across cultural settings (Aiko & Yoko, ; Borg, Kaukonen, Joukamaa & Tamminen, ; Bourdon, Goodman, Rae, Simpson & Koretz, ; Kremer et al , ; Lai et al , ; Maurice‐Stam et al , ; Niclasen, Teasdale, Andersen, Skovgaard, Elberling & Obel, ; Tobia & Marzocchi, ; Woerner, Becker & Rothenberger, ). Hence, to use the SDQ in research for cross‐country comparisons of children’s mental health problems or in paediatric care as an instrument to identify children with mental health problems, population‐specific norms and percentile cut‐off values are needed (Goodman et al , ).…”
Section: Aim and Hypothesesmentioning
confidence: 99%
“…The average total score on the parent-reported SDQ (SDQ-P) (41) was comparable to the scores of clinical samples (49,52,56). Most parents (69.0%) observed an increased level of psychosocial problems in their child (cutoff ≥14).…”
Section: Parent-reportedmentioning
confidence: 85%